Approach to the organization of decision support in the formulation of innovative regional development strategies applying adaptive-simulation model - L. Chernyakhovskaya; M. Nizamutdinov; V. Oreshnikov; A. Atnabaeva (Управление)
The issues of formation of the decision support system in the field of regional development management have been considered. The presented review of the existing approaches in this field testifies on the one hand to their diversity, and on the other hand, it allows us to draw a conclusion about the need to solute a number of methodological and practical issues of decision support in terms of innovative development of regions. On this basis, the goal of the research is to develop the concept of a decision support system to substantiate the parameters of the innovative strategy of regional development based on adaptive mechanisms for coordinating the interests of economic agents.The research methodology is based on the synthesis of different approaches in the framework of integration into the structure of adaptive simulation models of problem-oriented knowledge bases, as well as intelligent technologies for processing semistructured information, using to find decisions in the process of formation and adjustment of parameters of management of innovative development of the region. The result of the study is a theoretical justification for the development of problem-oriented DSS, including a description of the interrelated stages, determining the main design features of this toolkit.As a part of the study, a conceptual scheme of implementation of the decision support system in the field of management of regional innovative development has been proposed, the key functional blocks of the proposed tools have been described, the place of existing tools in the structure of the regional development management system has been determined, the possibilities of its use in the formation of forecast-planned assessments of regional development, as well as the evaluation of the effectiveness of alternative management actions, have been shown.In our opinion, the proposed tools will expand the possibilities of applying the management theory and decision support methods, intelligent information technology, economic and mathematical methods, modern computer simulation technologies for strategic planning of socio-economic systems of macro- and meso-level. In practice, the tools can be interesting for public authorities to solve problems in the formulation of innovative regional development strategies for the Russian regions, the formation of medium-term forecasts and the justification of the parameters of social, economic and budgetary policy.